Air pollution: A threat to health tourism development in the Islamic Republic of Iran (case study: Ilam city) - S. S. Hosseini; M. Taghvaei; E. S. Seidaiy; Y. Gholami; Z. V. Ataev (Юг России: экология, развитие)
Aim. Considering the high capability of Ilam province in the development of health tourism as indicated in its active border crossings with Iraq and the response to the recent epidemic, it was deemed necessary to identify the risks of air pollution on the health of tourists.Materials and Methods. During 2008‐2018, data on five primary air pollutants during 2008‐2018 were identified by literature research and by referring to the relevant monitoring organizations. Data analysis was performed by the Full permutation polygon synthetic indicator model, while Excel and MATLAB software were used to display data.Results. The findings of the study revealed that despite the application of the Land Use Planning Document, average suspended particulate matter of less than 10 microns ranked second after sulphur dioxide (SO2), in terms of the contribution to air pollution and instability in Ilam City during the 11 years in question (excluding 2008 and 2009).Conclusions. The link between air pollution and the development of health tourism on the one hand and the emergence of an epidemic on the other has recently necessitated a new concept of health, tourism and welfare in relation to the environment with the aim of achieving a healthy environment for visiting tourists.